STUDY AND ANALYSIS OF CONSUMER BUYING BEHAVIOR IN RETAIL MARKET - Dubey, Manish; Saini, Siddharth; Umekar, Srishti (International Journal of Engineering Technologies and Management Research, 2016)
The aim of this study are determining the impact of the most used tools of sales promotion in retail sector such as coupons, sample, price discount and buy one get one free on consumer buying behavior from two aspects are brand switching and customer loyalty. Consumer promotions should stimulate purchases, sustain brand-name recognition, and gain audience participation. Themes are underlying messages. Media should be selected. In this way include direct mail, newspapers, magazines, television, the personal sales force, and group meetings. The duration of a sales promotion is set. The feasibility of shared sales promotions is weighed.